2007
DOI: 10.1590/s0100-41582007000300003
|View full text |Cite
|
Sign up to set email alerts
|

Análise de risco das mudanças climáticas globais sobre a sigatoka-negra da bananeira no Brasil

Abstract: O conhecimento dos prováveis impactos das mudanças climáticas globais sobre a ocorrência de doenças de plantas é de grande importância para o setor agrícola, pois permite a elaboração de estratégias de controle. O presente trabalho teve por finalidade estudar os possíveis impactos das mudanças climáticas sobre a sigatoka-negra da bananeira, por meio da elaboração de mapas de distribuição da doença confeccionados a partir dos cenários disponibilizados pelo IPCC. Os mapas mostraram que haverá redução da área fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 12 publications
4
24
0
7
Order By: Relevance
“…These changes will be gradual for the decades of 2020, 2050 and 2080, with some exceptions that will be presented later in this paper. Results are in agreement with Ghini et al (2007) who predicted that there will be a reduction of the favorable area to BS in Brazil in the future. Other authors also showed changes on the spatial distribution of favorability classes for other pathosystems in the future, like Carter et al (1996), Boag et al (1991), Brasier & Scott (1994) and Brasier et al (1996).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These changes will be gradual for the decades of 2020, 2050 and 2080, with some exceptions that will be presented later in this paper. Results are in agreement with Ghini et al (2007) who predicted that there will be a reduction of the favorable area to BS in Brazil in the future. Other authors also showed changes on the spatial distribution of favorability classes for other pathosystems in the future, like Carter et al (1996), Boag et al (1991), Brasier & Scott (1994) and Brasier et al (1996).…”
Section: Resultssupporting
confidence: 90%
“…Complete results for simulations based on the six different climate change models and the "multimodel ensemble" are presented in Tables 2 to 4. The intervals used in this study to characterize classes of favorability to BS were adequate because the obtained maps considering the current climate (Figure 1) were in agreement with data available in the literature (Mourichon et al, 1997;Carlier et al, 2000;Ghini et al, 2007). The pathogen produces conidia and ascospores and both play roles in the spread of the disease.…”
Section: Resultssupporting
confidence: 78%
“…The climate change risk analysis for the Blacksigatoka of banana (caused by Mycosphaerella fijiensis) was studied by Ghini et al (2007), elaborating disease distribution maps assembled from scenarios and GCM data provided by the IPCC (2001). The maps revealed that there will be a reduction in the favorable area for the disease in Brazil.…”
Section: Geographical and Temporal Distribu-tionmentioning
confidence: 99%
“…Neste patossistema, os autores observaram que a região do espectro do visível foi a que melhor detectou a ocorrência do patógeno nos diferentes níveis de danos testados. A utilização de imagens de sensoriamento remoto permitiu espacializar o risco de ocorrência da doença em função do pixel, o que tornou possível realizar inferências em pequenas propriedades, diferentemente do trabalho desenvolvido por Ghini et al (2007), em que os autores fizeram uma projeção de cenários do comportamento da Sigatoka-negra em função das mudanças climáticas e considerando áreas continentais.…”
Section: Resultsunclassified